Fluvial architecture and depositional system of the Miocene molasse sediments, Shakardarra formation, southeastern Kohat, Pakistan - Abbasi, Iftikhar Ahmed (Journal of Himalayan Earth Sciences, 1994)
The Neogene molasse sediments in southeastern Kohat area are divided into two groups, the Rawalpindi, and the Siwalik groups. The Siwalik Group in the study area, around Shakardarra town, is a coarsening upward sequence of silt dominated Chinji Formation, sand dominated Shakardarra Formation, and polymictic conglomerate dominated Indus Conglomerate Formation. The Shakardarra Formation is comprised of sandstone-siltstone in the basal part, dominantly sandstone in the middle part and sandstone-conglomerate in the upper part. The major sandstone-bodies, on average, are up to 15m thick and many km in lateral extent in the lower part, whereas, up to 100m thick and tens of kilometres in lateral extent in the middle and upper parts. The sandstone-bodies are multistoried, and are characterized by in channel lithofacies such as plane-bedding, low angle plane-bedding and trough cross-bedding. A number of bar macroforms and channel features of different hierarchal order have been observed in the sandstone-bodies. A high energy braided River system is suggested for the deposition of the sediments. The paleo river system was flowing approximately parallel to the present day Indus river, and entered the foreland basin through the study area at least since last 10 ma.